Situating mental health work in place: Qualitative findings from interviews with Veterans in Southeastern Louisiana and Northern California. (September 2017) - Abraham, Traci H.; Koenig, Christopher J.; Zamora, Kara; Hill, Coleen; Uddo, Madeline; Kelly, Adam P.; Hamilton, Michelle F.; Curran, Geoffrey M.; Pyne, Jeffrey M.; Seal, Karen H.
Abstract: Most chronic illness management occurs outside clinics and hospitals, in the everyday lives of individuals. We use data from semi-structured interviews with 37 veterans from Southeastern Louisiana and Northern California to illustrate how "health work" for mental health concerns are shaped by place. Using health work as an orienting concept for analysis, we discerned variation between the two study sites in how Veterans used interacting with the natural environment, cultivating time alone, and religious practice to manage their mental health and well-being. Through these findings, we advocate for a situated notion of health work that is mindful of how health-related behaviors are shaped by place and the attributes that constitute place. Highlights: We used semi-structured interviews to explore mental health work among 37 Veterans. Participants described everyday behaviors used to manage health and well-being. Analysis revealed variation in health work strategies between sites. Cross-site differences in mental health work can be attributed to place. Through our findings, we advocate for a situated notion of health work.